Performance of selected chemical compounds in eliciting feeding of Asian buffalo leech, Hirudinaria manillensis - Teh, Jun Chin; Kamarudin, Mohd Salleh; Abd Rahim, Abdullah; Saad, Che Roos (Academic Journals, 2011)
The understanding of appetitive and foraging behavior of medicinal leeches is important for successful breeding and culture of healthy leeches. This study was conducted to determine the response of Asian buffalo leech, Hirudinaria manillensis for combinations of selected chemical compounds. Five solutions with different combinations of sodium chloride, arginine, glycine and glucose were filled into rubber sacs and fed to the leeches in 3 replicates each. Heparinized cattle blood was used as the control. The percentages of leech that approached the sacs and the average volume consumed per individual were estimated. After feeding, the survival of leeches in each treatment was monitored daily for seven days. The results showed that a solution containing 150 mM sodium chloride, 1 mM L-arginine, 50 mM glycine and 1 mg mL-1 glucose gave significantly higher (p<0.05) approach percentage and feed consumption than other solutions. Its performance was equivalent to the cattle blood. Poor feeding consumption was observed when only L-arginine or glycine were added to the saline solution. Nevertheless, mortality up to 40% was observed among the feeding leeches while the survival of non-feeding leeches was nearing or at 100%.